A choice of weights for convex combination methods in estimating partial derivatives - Yean, Sang Ooi; Chang Hooi Tuang, Lawrence; Ya, Ping Wong; Abd R Mt Piah (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to pulisher's homepage at http://ieeexplore.ieee.org